G protein mutations in pituitary tumors: A study on Turkish patients - (:unkn) unknown (My University, 2003)
Activating mutations of the G proteins, G8α (gsp) and Gi2a. (gip) have been reported in subsets of pituitary tumors. The objective of the study was to assess the frequency of gsp and gip mutations in pituitary tumors from Turkish patients and to investigate the possibility of mutations of protein kinase A catalytic subunit (PKAC) that activates the downstream effectors of adenylyl cyclase. PCR-amplified genomic DNA was analyzed for the presence of mutations in codons 201 and 227 of Gsα, codon 179 and 205 of Gi2α and codon 196 of PKAC, by single strand conformation polymorphism analysis, allele-specific oligonucleotide hybridization and DNA sequencing. Twenty-two patients from Turkey, 15 females and 7 males were investigated; 7 somatotroph adenomas, 7 clinically non-functioning tumors, 7 prolactinomas and 1 corticotroph adenoma. G protein mutations were identified in 6 of 22 (27.3%) pituitary tumors. Four tumors (3/7 somatotroph adenomas, 43%, 1/7 clinically non-functioning tumor) demonstrated gsp mutations at codon 201 arginine to cysteine and one recurrent somatotroph adenoma demonstrated a mutation of the Gi2α, gene at codon 193 lysine to arginine. One tumor exhibited a C to T variation in the intervening sequence between codons 179 and 205 of the Gi2α gene. No mutations at codon 227 of Gsα, codons 179 and 205 of Gi2α, and codon 196 of the PKAC gene were identified.
Keywords: Adenylyl cyclase; G protein mutations; Pituitary tumors; Protein kinase A